Clinical Profiles and Il-6 Level Analysis of Critical Covid-19 Patients Receiving Lopinavir-Ritonavir - Triyono, Erwin Astha; Rehatta, Nancy Margarita; , Nabilah; Tan, Feriawan (Folia Medica Indonesiana, 2023)
Highlights: 1. Lymphocyte, procalcitonin, D-dimer and high IL-6 levels in COVID-19 patients are associated with a poor prognosis. 2. IL-6 serial measurement for COVID-19 patients may be a potential indicator for evaluating the severity and patient outcome. Abstract The COVID-19 pandemic has affected over 760 million individuals worldwide, resulting in more than 6.8 million reported deaths. Early detection of patient deterioration can assist in predicting outcomes and prioritizing healthcare services based on evidence-based indicators. Interleukin-6 (IL-6) is a cytokine that plays a role in the inflammatory process, making it a potential parameter for assessing a patient's inflammatory state. This study aimed to analyze the characteristics, laboratory profiles, and IL-6 levels of COVID-19 patients. This study used a retrospective cohort study design with medical record data. The characteristics (n=68) and IL-6 levels (n=52) of the patients on the first, third, and sixth days of treatment were recorded consecutively. The mean age of the patients was 49 years, with the majority being male (72%) and the most prevalent comorbidity being hypertension (29%). The average duration of hospitalization was 10.94 days. Shortness of breath was the most commonly reported symptom (45.6%). The medians of neutrophil-lymphocyte ratio, C-reactive protein, procalcitonin, ferritin, and D-dimer were above normal. Significant differences were observed in lymphocytes (p=0.046), procalcitonin (p=0.023), and D-dimer (p=0.000) between survivor and non-survivor patients. Significant dynamic changes in IL-6 levels were observed from the first day to the sixth day (p=0.014) and from the third day to the sixth day (p=0.041). In conclusion, risk stratification, laboratory profiles, and IL-6 levels play a role in assessing the severity and outcomes of COVID-19 patients.